2013
DOI: 10.1016/j.pestbp.2013.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Sulfoxaflor and the sulfoximine insecticides: Chemistry, mode of action and basis for efficacy on resistant insects

Abstract: The sulfoximines, as exemplified by sulfoxaflor ([N-[methyloxido[1-[6-(trifluoromethyl)-3-pyridinyl]ethyl]-λ(4)-sulfanylidene] cyanamide] represent a new class of insecticides. Sulfoxaflor exhibits a high degree of efficacy against a wide range of sap-feeding insects, including those resistant to neonicotinoids and other insecticides. Sulfoxaflor is an agonist at insect nicotinic acetylcholine receptors (nAChRs) and functions in a manner distinct from other insecticides acting at nAChRs. The sulfoximines also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
181
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(194 citation statements)
references
References 26 publications
8
181
0
5
Order By: Relevance
“…Metabolites of flupyradifurone include the 6-chloronicotinic acid (6-CNA), common to most neonicotinoids. A very similar situation is observed for sulfoxaflor, introduced as a sulfoximine insecticide by the manufacturer (Sparks et al 2013). As can be seen in Fig.…”
Section: Mode Of Action and Metabolismsupporting
confidence: 77%
“…Metabolites of flupyradifurone include the 6-chloronicotinic acid (6-CNA), common to most neonicotinoids. A very similar situation is observed for sulfoxaflor, introduced as a sulfoximine insecticide by the manufacturer (Sparks et al 2013). As can be seen in Fig.…”
Section: Mode Of Action and Metabolismsupporting
confidence: 77%
“…8 However, there is no literature available on analytical methods for the determination of sulfoxaflor residues in foods of animal origin. 9 Animal matrices are considerably complicated as they are rich in fat, protein, and some other lipophilic compounds that are easily coextracted with the target analytes. 10 Thus, it is extremely difficult to effectively purify the samples.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[16,17] The insecticidal mechanism of sulfoxaflor is reliant on the agonistic action towards the insect nicotinic acetylcholine receptor (nAChR). [18][19][20][21] The effects of sulfoxaflor on the insects include excitatory symptoms, such as tremors, followed by paralysis and mortality, thereby suggesting that the molecule acts on the insect nervous system. [19] Recent studies have reported that the sulfoximine structure can improve the insecticidal activities of anthranilic diamides.…”
Section: Introductionmentioning
confidence: 99%